Aerosolized corticosteroids to prevent postoperative sore throat in adults: A systematic review and meta‐analysis. Issue 3 (14th October 2018) - Kuriyama, Akira; Maeda, Hirokazu; Sun, Rao
Abstract : Background: Postoperative sore throat negatively affects patient recovery and satisfaction levels. We conducted a systematic review and meta‐analysis to assess the efficacy and safety of aerosolized corticosteroids in the prevention of postoperative sore throat in adults undergoing tracheal intubation for surgery. Methods: We searched Medline, EMBASE, China National Knowledge Infrastructure, and the Cochrane Central Register of Controlled Trials for eligible studies from inception to 13 May 2018. We included randomized controlled trials that assessed the efficacy and safety of aerosolized corticosteroids, compared either with non‐analgesic or analgesic controls, in adults undergoing tracheal intubation for surgery. Incidence and severity of sore throat 24 hours postoperatively and adverse events were the primary outcomes. Results: Nine randomized controlled trials involving 984 patients were included. Compared with non‐analgesic control, aerosolized corticosteroids were associated with a reduced incidence (risk ratio [RR], 0.39; 95% confidence interval [CI], 0.26‐0.58) and were likely associated with decreased severity (standardized mean difference [SMD], −0.96; 95% CI, −2.52, 0.59) of postoperative sore throat. Among these, four trials reported that there were no adverse events. Trial sequential analysis (TSA) suggested that the evidence on the incidence of postoperative sore throat, in comparison with the non‐analgesic control, was not definitive (TSA‐adjusted CI, 0.07‐1.98). The GRADE quality of evidence on each outcome was very low. Conclusions: Aerosolized corticosteroids may be superior to non‐analgesic methods in preventing postoperative sore throat, but the evidence for efficacy and safety is still limited and not definitive.